A basal ornithopod dinosaur from the Cenomanian of the Czech Republic. (2nd September 2018) - Madzia, Daniel; Boyd, Clint A.; Mazuch, Martin
Abstract : During their long evolutionary history, neornithischian dinosaurs diverged into several clades with distinctive adaptations. However, the early evolution within Neornithischia and the resolution of the phylogenetic relationships of taxa situated near the base of the clade remain problematic. This is especially true for those taxa traditionally placed at the base of Ornithopoda, either as 'hypsilophodontids' or at the base of the diverse clade Iguanodontia. Recent studies are improving our understanding of the anatomy and relationships of these taxa, with discoveries of several new non-ankylopollexian ornithopods from South America and Europe providing key insights into early ornithopod evolution and palaeobiogeography. Here, we describe a new basal ornithopod, Burianosaurus augustai gen. et sp. nov., based on a well-preserved femur from the upper Cenomanian strata (Korycany Beds of the Peruc-Korycany Formation) of the Czech Republic. The new taxon is diagnosed by a unique suite of characters and represents the only occurrence of a Cenomanian non-avian dinosaur in Central Europe north of the Alpine Tethyan areas. Histological examination of the type specimen reveals the presence of a loosely packed Haversian system which suggests relatively mature bone from a possible young adult. Phylogenetic analyses of two different data sets, selected to test the placement of B. augustai in various parts of the neornithischian tree, reconstruct B. augustai as a basal ornithopod, firmly nested outside Ankylopollexia. These results also support a diverse Elasmaria as a basal clade within Ornithopoda and reconstruct Hypsilophodon outside Ornithopoda as the sister taxon to Cerapoda. However, the relationships of 'hypsilophodontids' within Neornithischia remain contentious. http://zoobank.org/urn:lsid:zoobank.org:pub:D28A9FB8-A253-4032-8710-4F51668A1E4F